2022
DOI: 10.1101/2022.04.26.489530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationships between mediolateral step modulation and clinical balance measures in people with chronic stroke

Abstract: BackgroundMany people with chronic stroke exhibit walking balance deficits, which are linked with increased fall risk and decreased balance confidence. One potential contributor to these deficits is a decreased ability to adjust where the paretic foot is placed based on pelvis motion, which is an important factor in mediolateral walking balance.ObjectiveThe objective of this study was to investigate altered stepping behavior for steps taken with the paretic leg, and to explore the relationship between this beh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Since the current study aims at giving better insight into what earlier found improvements in the degree of foot placement control [12, 17] reflect, as well as whether the effects of sensory augmentation and force-field perturbations could complement each other, further investigating the relationship with gait stability is beyond the scope of this study. Another study, has already established a link between foot placement outcome measures and clinical outcome measures [25]. Future work is needed to gain more insight into which (foot placement) outcome measures should improve for a gait stability training to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Since the current study aims at giving better insight into what earlier found improvements in the degree of foot placement control [12, 17] reflect, as well as whether the effects of sensory augmentation and force-field perturbations could complement each other, further investigating the relationship with gait stability is beyond the scope of this study. Another study, has already established a link between foot placement outcome measures and clinical outcome measures [25]. Future work is needed to gain more insight into which (foot placement) outcome measures should improve for a gait stability training to be effective.…”
Section: Discussionmentioning
confidence: 99%